The Russian revolution of 1905 in transcultural perspective: identities, peripheries, and the flow of ideas - Fischer von Weikersthal, Felicitas; Grüner, Frank; Hohler, Susanne (The Allan K. Wildman Group Historical series, 2013)
Shifting identities. Priests and revolution: the parish clergy of Vladimir in 1905 / Gregory L. Freeze ; Peasant economic interests in 1905 / Franziska Schedewie ; Jewish self-defense, revolution, and pogrom violence in 1905 / Gerald Surh ; Crystallizing memory: how Russian Jews in the first emigration canonized their legacy / Brian Horowitz -- Revolution and civil society. Radical right civil society / Susanne Hohler ; Revolutionary hinterland: transformations of Jewish associational life in the Kingdom of Poland, 1904-06 / Franìois Guesnet ; (Re-)locating jewishness and representing Jewish community in Riga before and after 1905: urban elites, local politics, cultural self-representations, and intra-communal conflict / Felix Heinert -- Center and peripheries. Distant allies: the revolutionary movement and native resistance in the North Caucasus 1905-13 / Lothar Maier ; A continuum of crisis? The Kingdom of Poland in the shadow of revolution (1905-15) / Malte Rolf ; The Russian revolution of 1905 at the periphery: the case of the manchurian city of Harbin / Frank Grüner ; Autonomy, sovereignty, class struggle? Motifs of rioting in Finland 1905-06 / Ralph Tuchtenhagen ; Loyalty, minority, monarchy: the Baltic German press and 1905 / Katja Wezel ; Mutinous soldiers, striking workers and middle-class regionalists: Siberia in the revolution of 1905-07 / Dittmar Dahlmann -- The revolution in media and culture. The revolution of 1905 in Polish literature: Henryk Sienkiewicz's Wiry (Whirls) and Andrzej Strug's Dzieje jednego pocisku (The story of one bomb) / Christoph Garstka ; The revolution of 1905, art and Soviet propaganda / Felicitas Fischer von Weikersthal -- The international dimension and flows of concepts and ideas. China and the Russian revolution of 1905 / Gotelind Müller ; Revolution, diplomacy, and the media: Russian and British liberals in 1906 / Raphael Utz ; Russia's finances and 1905 / Peter Waldron ; The conquest of bread: Japanese early socialism and the Russian revolution of 1905 as an inspiration / Maik Hendrik Sprotte